SUDUT PANDANG ALIRAN HUMANISTIK TERHADAP MODEL PENDIDIKAN ANDRAGOGI - Bayu, Bayu (Universitas Prof. Dr. Moestopo (Beragama), 2009)
In-generaltherearetwounderstandthatteachingpedagogythatisvalidand andragogy.Andragogyunderstandis theplacetostudyparticipantsas